Wirtschaft, Arbeit und Leben mit und nach der Corona-Krise - Wannöffel, Manfred; Gensterblum, Yves (2022)
This anthology contains an interdisciplinary analysis of crisis phenomena and social challenges through historical comparisons and interdisciplinary reflection in order to causally understand the deeper dynamics of social and political processes as a result of the coronavirus pandemic. From an academic perspective, a variety of questions arise about structural challenges in the economic, working and living worlds, which are discussed here within the framework of an interdisciplinary and transdisciplinary dialogue between historians, economists, psychologists and sociologists. With contributions by Andrea Bianchi-Weinand, Yves Gensterblum, Thomas Haipeter, Rolf G. Heinze, Annette Kluge, Stefan Müller, Greta Ontrup, Christina Reinhardt, Wiebke Roling, Michael Roos, Kathrin Schäfers, Jochen Schroth and Manfred Wannöffel.